Reconsiderando las estrategias de desarrollo automotor en Argentina a la luz de la experiencia de la ASEAN - Perez Artica, Rodrigo (2022)
We compared the Argentinian automotive industry’s trajectory since 2000 with those cor-responding to three ASEAN economies: Malaysia, Indonesia, and Thailand. We aimed to identify factors explaining the divergence among the four cases and to draw valuable conclu-sions for the re-design of Argentinian automotive policy. First, we considered the productive and foreign trade performance among the four cases. We then reviewed key industrial policies conducted over the period. Comparative analysis highlights the Thai experience, which post-ed outstanding performance on both industrial expansion and trade surplus. Moreover, we ex-amined the high potential for selective policies incentivizing specific products and technolo-gies, which can promote private strategies more aligned with macroeconomic stability and industrial development in Argentina.